Embedding Anglocentric Perceptions of the World: The Falklands-Malvinas Binomial in the News - Valdeón, Roberto (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
This paper aims to examine the clash between languages and cultures as identified in the treatment of news events, with particular reference to the Falklands, or Malvinas in their Spanish denomination, in British and Spanish Internet news portals. English, as a global language, and Spanish, as its main European rival, exemplify a conflict between two languages and cultures that attempt to achieve or maintain world dominance, a battle that has been taken to the Internet arena in recent years. Thus, El País newspaper launched an English version for their Internet readers whereas the BBC produced a Spanish version of its English news service.The conflict between the two languages is decisive when reporting on highly sensitive areas in each culture, such as the issue of Gibraltar’s sovereignty or the news events originating in or around the Falkland Islands. The paper pays particular attention to the latter and the way in which translation is embedded within or is part of the conflict itself. For that purpose, the paper surveys the reports posted in the Spanish news web sites Abc, El País, and El Mundo, on the one hand, and the English portals of The Guardian, The Times, Daily Telegraph, The Independent and the BBC on the other. The results will be compared with the translated news in the English edition of El País and in the Spanish version of the BBC (BBCMundo) respectively to determine the position of the two media with regards to this issue.